The Attitude of the SME Towards Islamic Banking : The Case of SMEs in the South-West Region of Tunisia - Daghsni, Olfa; HENCHIRI, Jamel Eddine (Journal of Ecohumanism, 2025)
The purpose of this research is to ensure the factors that influence the attitude of SMEs towards Islamic banking services. The data of 28 entrepreneurs of SMEs were collected through an interviewer-administered questionnaire using a random sampling technique. This study uses a theoretical model based on the theory of planned behavior. To analyze the data obtained from the questionnaire, exploratory factor analysis techniques are used. The study has found significant impact of the quality of service, knowledge of Islamic finance, religious belief and support for business on the attitude towards Islamic banking, among SMEs in the south- west region of Tunisia. The results identify important factors that Islamic can use to update their strategies to attract potential customers and expand their customer base by adopting innovative financial solutions for small and medium-sized enterprises (SMEs).